Intravenous regadenoson with aminophylline reversal is safe and equivalent to intravenous adenosine infusion for fractional flow reserve measurements. Issue 10 (22nd October 2018) - Edward, Justin A.; Lee, John H.; White, Christopher J.; Morin, Daniel P.; Bober, Robert
Abstract : Background: Small studies have shown that adenosine is equivalent to regadenoson when obtaining coronary fractional flow reserve (FFR) measurements. A study that also evaluates time and safety of aminophylline reversal of regadenoson effects has not been presented. Hypothesis: Reversal of regadenoson with aminophylline is safe and equivalent to adenosine for FFR measurements. Methods: Forty‐six consecutive patients who underwent clinically indicated FFRs at the time of coronary angiography were enrolled between 4/2012 and 5/2014. Each patient had FFR measured using adenosine 140 mcg/kg/min IV, and following return to baseline, FFR was measured using regadenoson 400 mcg IV, which then was reversed with aminophylline 150 mg IV. Time to baseline hemodynamics was measured. Agreement between the two assessments was compared using linear regression. Results: FFR results were similar with both agents ( R 2 = 0.935, P < 0.0001). Also, using the 0.80 cutoff for significantly depressed FFR, there was no divergence regarding studies' significance. After aminophylline reversal of regadenoson, hemodynamics returned to baseline in 111 ± 71 seconds. There were no unexpected side effects or complications. Conclusions: For FFR measurement, regadenoson and adenosine are equivalent hyperemic agents. Regadenoson with aminophylline reversal may be considered as an alternative to adenosine for FFR measurements.